KANDOUSHI PADA TUTURAN PELANGGAN DALAM SERIAL DRAMA IZAKAYA BOTTAKURI - -, Suyanti Natalia (Universitas Nasional, 2024)
This study aims to understand the meaning of the words spoken by the interlocutor. Speech has different meanings depending on the context and situation, including interjections. Interjections in Japanese are referred to as kandoushi. Kandoushi is a word that can express the feelings of the speaker. Through kandoushi theory, Masaoka and Takubo (1996: 60) state that there are two types of kandoushi, namely kandoushi which expresses feelings or Kandou and kandoushi which is used as a greeting or aisatsugo. The data in this research is the Japanese television drama series entitled